METODE PENDIDIKAN SHALAT PADA ANAK USIA 5-10 TAHUN DALAM KELUARGA - Sopiyana, Muhammad; Budiman, Septian Arief (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2018)
The application of education in the family environment is often an obstacle especially for parents, not least for parents who work as teachers, special methods are needed because what is faced is their own biological children, this study aims to obtain appropriate learning solutions and methods for prayer education in the family environment teacher, the research method used in this research is descriptive qualitative by collecting data through interviews, the results obtained from this study are prayer learning methods for teachers' children by using habituation and parental modeling to their children.